Production of Monoclonal Antibodies against Human Trefoil Factor 3 and Development of a Modified-Sandwich ELISA for Detection of Trefoil Factor 3 Homodimer in Saliva - Saichit Khummuang (2018)
© 2017 The Author(s). Background: Human trefoil factor (TFF) peptides consist of three members: TFF1, TFF2 and TFF3. TFF3 is the most abundant TFF peptide in saliva. TFF3 homodimer was suggested to be involved in apoptosis inhibition and malignancy. Determination of TFF3 homodimer expression profiles in saliva may lead to new information about oral biology and diseases. The objective of this study was to generate monoclonal antibodies (mAbs) against TFF3 and apply the produced mAbs for the establishment of ELISA for quantification of dimeric TFF3 in saliva. Results: With our modified hybridoma technique, three hybridoma clones producing anti-TFF3 mAbs having IgG isotype were generated. The mAbs were specific for TFF3 with no cross-reactivity to other TFFs. Using the generated mAbs, a modified-sandwich ELISA with high sensitivity for the quantification of dimeric TFF3 in saliva was developed. Using this ELISA, the amount of dimeric TFF3 in saliva could be measured. Conclusions: A modified-sandwich ELISA for the quantification of TFF3 dimeric form was established. The established ELISA will be a valuable tool for facilitating the investigation of the physiological roles and the diagnostic values of TFF3 in oral diseases. The concept of this modified-sandwich ELISA may be applied for the determination of other homodimeric peptides of interest.